A roda de conversa em diálogo com o círculo de cultura na educação infantil: a prática pedagógica de uma professora - Soares, Selma (2020)
The research’s object is the conversation circle in dialogue with the culture circle at early children education as a field of knowledge. This study was motivated by the following questions: how a preschool teacher, that teaches to 4-year-old children, develops the conversation circle in her daily practice? Do the conversation circles dialogue with the culture circles? The main goal of the research is to analyze if the pedagogical practice of the teacher, concerning the conversation circle, dialogues with the culture circles. As specific goals of the research, there are: verifying how a preschool teacher, that teaches for 4-year-old children, develops the conversation circle in her daily practice; identifying the topics brought by the children in this activity and if they are developed by the teacher; identifying if all the children participate in the activity; and verifying the teacher’s behavior in this context. It is understood that small children can offer contributions to the creation of a dialogical education that benefits the exercise of the citizenship; therefore, it is assumed that it is possible to develop conversation circles that dialogues with culture circles as long as the teacher is open to the dialogue and to the listening and respect the knowledge of the small ones. The universe of the research is a School of Early Childhood Education – “Escola Municipal de Educação Infantil”, in Portuguese (Emei) – eastern zone of São Paulo city. The participants of the research are 4-year-old children of kindergarten and the regent teacher. The methodology has a qualitative approach, and the tools for data collection are the participative observation, audio recorder of the conversation circles accomplished by the teacher and circle’s photos. The theoretical frame is mostly based in Paulo Freire’s ideas, in dialogue with authors of childhood studies. The data indicate that is possible to develop the conversation circles in a dialogue with the culture circles in early childhood education, once that the teacher’s practice, participant of the research, values the listening and the rapprochement with the children in the dialogue’s moments – and outside them –; respects the knowledge prevenient of each child’s experiences; and values the children’s initiative in researching and in experimenting life, besides being willing to continuously reviewing her practice through action-reflection-action. However, it was observed, in some moments, that the teacher did not wait children’s answers and hypothesis, answering in advance. Yet, this attitude did not mischaracterize children’s knowledge – after all, in human incompleteness and inconclusion, this can happen. In most of the activities, the teacher was able to stay away from the commonplace, providing a dialogical practice, being willing to an attentive listening and qualifying her practice as a childhood educator. In order to perform the culture circle with the children, it will be necessary, on the part of the teacher, a deeper study about this category. Thus, as an intervention proposal, it was pursued with the teacher to plan culture circles and develop them with the children in a near future.